2021
DOI: 10.21608/ejchem.2021.49815.3027
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Design Optimization of Microwave Digestion for Macro and Microelements in Pregnant Women and Diabetics Multivitamin/Multielement Preparations by Inductive Coupled Plasma Mass Spectrometry (ICPMS)

Abstract: In the present work, the microwave digestion procedure for the determination of Ca, Co, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Se, V and Zn in multivitamin/multielement (MVM) preparations used for pregnant women and diabetics employing ICP-MS, was optimized by factorial design 3 3 (27 runs). The microwave digestion conditions temperature (160, 180 and 200ºC), acid mixture volume (3.9, 5.2 and 6.5 ml) and radiation period (10, 15 and 20 min) were selected as factors. Moreover, a multiple response (MR) was built to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…At temperatures less than 190 °C, we observed that the solutions resulting from digestion were yellowish in color with suspended solid particles. Other studies have reported the same observation [30,31]. At temperatures above 215 °C, we observed explosive conditions inside the microwave equipment, probably because of H 2 O 2 decomposition [32].…”
Section: Optimization Of the Microwave-assisted Digestionsupporting
confidence: 88%
“…At temperatures less than 190 °C, we observed that the solutions resulting from digestion were yellowish in color with suspended solid particles. Other studies have reported the same observation [30,31]. At temperatures above 215 °C, we observed explosive conditions inside the microwave equipment, probably because of H 2 O 2 decomposition [32].…”
Section: Optimization Of the Microwave-assisted Digestionsupporting
confidence: 88%